(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2018)
«Preventive reconciliation» is the process of reestablishing fair relations motivated by the bond of love of fathers and mothers towards sons and daughters and vice versa. It is this intergenerational bond of love that helps most to prevent injustices, to leave the circle of violence and to promote a positive peace. Preventive reconciliation involves going beyond the prevention of ill treatment towards the promotion of good treatment: proactively sustaining a positive peace that protects and cares for the child in an integral way in all his needs. Therefore, the absence of bad treatment is not «good treatment»; and preventive reconciliation implies one and the other. The right to good treatment based on the dignity of the person (in our opinion, good treatment is based on the Convention of the Child) is the framework within which we must understand preventive reconciliation as an exercise in which children do not only adults, play a proactive role.